Evaluation of an Interdisciplinary Curriculum Teaching Team-based Palliative Care Integration in Oncology - Head, Barbara A. (J Cancer Educ, 2016)
For students of the health care professions to succeed in today's healthcare environment, they must be prepared to collaborate with other professionals and practice on interdisciplinary teams. As most will care for patients with cancer, they must also understand the principles of palliative care and its integration into oncology. This article reports the success of one university's effort to design and implement an interdisciplinary curriculum teaching team-based palliative care in oncology which was mandatory for medical, nursing, social work and chaplaincy students. Quantitative evaluation indicated that students made significant improvements related to palliative care knowledge and skills and readiness for interprofessional education. Qualitative feedback revealed that students appreciated the experiential aspects of the curriculum most, especially the opportunity to observe palliative teams at work and practice team-based skills with other learners. While there exist many obstacles to interprofessional education and hands-on learning, the value of such experiences to the learners justifies efforts to initiate and continue similar programs in the health sciences.